One-shot dalbavancin infusion combined with vacuum-assisted closure of Crohn’s anal fistulas - Jacek Hermann; Hanna Tomczak; Barbara Kołodziejczak; Dorota Mańskowska-Wierzbicka; Tomasz Banasiewicz; Ryszard Marciniak (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Hermann J, Tomczak H, Kolodziejczak B, Mańskowska-Wierzbicka D, Banasiewicz T, Marciniak R. One-shot dalbavancin infusion combined with vacuum-assisted closure of Crohn’s anal fistulas. Turk J Gastroenterol 2019; 30: 113-4.